Basilic Vein Mobilization for Brachio-Basilic Arterio-Venous Fistula in Dialysis - Jabir, . Sabah Noori; .Al-Assal*, . Muthanna D.R; Shini *, Hazim . J.; ALmudaffar, . Saif S. (AL-Kindy College Medical Journal, 2015)
Background: The first and second choice for vascular access in patients with end stage renal disease (ESRD) is radio cephalic and brachio cephalic arteriovenous fistula (AVF).In patients with failed previous AVF e or poorly visualized or impalpable cephalic veins, the basilic vein can be mobilized and superficialized to create an AVF with the brachial artery.Objective: The aim of this study is to report our experience at the Vascular Surgery Department/ Surgical Specialty Hospital in brachio-basilic (BB) vascular access for hemodialysis.Methods: From January 2006 to December 2009, 31 patients with ESRD whose cephalic veins were thrombosed or impalpable or had previous unsuccessful vascular access procedures were referred to the Vascular Surgery Department/Surgical Specialty Hospital for creation of vascular access. Brachio - basilic mobilization AVF was offered to them. There were 20 females and 11 males. Their ages ranged from 12 to 70 years with a mean of 40. following a careful clinical assessment of the patients, particularly their upper limb superficial veins, Doppler study of both subclavian veins was done to all patients; those with a vein stenosis exceeding 40% were excluded from the study. All patients had mobilization of basilic vein under general anesthesia via a hooky racket incision on medial aspect of upper arm extending from the axilla to the antecubital fossa. The vein is tunneled subcutaneously and anastomosed end to side to brachial artery. The postoperative condition was monitored looking for any complication. The follow up period lasted for 6 months.Results: nineteen patients (61.3%) had left-sided operations. All fistulae except one functioned well primarily (a success rate of 96.8%). One patient had primary thrombosis of the fistula while another patient developed an aneurysm of the AVF 4 months after the operation. The remainder had a smooth non-complicated postoperative course. All fistulae matured and were ready for cannulation in 6 weeks and remained functioning during the 6 months of follow up.Conclusion:: Brachio-basilic AV fistula with anterior basilica vein mobilization is an acceptable option for dialysis with good success rate and fewer complications